2020
DOI: 10.1007/s10340-020-01272-0
|View full text |Cite
|
Sign up to set email alerts
|

Host preference of three Asian larval parasitoids to closely related Drosophila species: implications for biological control of Drosophila suzukii

Abstract: Insect parasitoids can attack phylogenetically related hosts that share similar physiological properties and defense mechanisms and, more importantly, overlapping ecological niches. Here, host preferences of three parasitoids, Asobara japonica (Hymenoptera: Braconidae), Ganaspis brasiliensis and Leptopilina japonica (Hymenoptera: Figitidae), were examined on two closely related hosts, Drosophila suzukii and D. melanogaster (Diptera: Drosophilidae). Each parasitoid's rate of successful parasitism (or offspring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 51 publications
(79 reference statements)
1
26
0
1
Order By: Relevance
“…Results are presented as mean ± SE. As described in Biondi et al (2021) for assessing the impact of fly larvae in fruit versus artificial diet, the impact of host species on the development of parasitoid offspring was compared using "Successful Rate of Parasitism" (SP) to determine the probability that a parasitized host would give rise to an adult wasp. SP is calculated as ep/ (ef − efp), where ep = number of emerged parasitoids, ef = the average number of emerged flies in the absence of parasitoids (control), and efp = number of emerged flies in the presence of parasitoids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results are presented as mean ± SE. As described in Biondi et al (2021) for assessing the impact of fly larvae in fruit versus artificial diet, the impact of host species on the development of parasitoid offspring was compared using "Successful Rate of Parasitism" (SP) to determine the probability that a parasitized host would give rise to an adult wasp. SP is calculated as ep/ (ef − efp), where ep = number of emerged parasitoids, ef = the average number of emerged flies in the absence of parasitoids (control), and efp = number of emerged flies in the presence of parasitoids.…”
Section: Discussionmentioning
confidence: 99%
“…The two figitid species were kept with males from adult emergence and were assumed to be mated, whereas virgin female A. japonica were used as this species has a strongly female-biased sex ratio and the tested strain was primarily parthenogenetic (Daane et al 2016). Details on some aspects of the biology of these parasitoids, reared on D. suzukii, have been presented previously (Biondi et al 2021;Girod et al 2018a, c;Wang et al 2018Wang et al , 2019aWang et al , 2021.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, the generalist parasitoid T. drosophilae showed no differential preference for D. melanogaster or D. suzukii pupae (Wang et al 2016). Similarly, a recent study by Biondi et al (2020) showed that the larval parasitoids, Asobara japonica Belokobylskij (Hymenoptera: Braconidae), Leptopilina japonica Novković & Kimura and Ganaspis brasiliensis (Ihering) (Hymenoptera: Figitidae), respond to fruit volatile cues associated with the presence of either D. suzukii or D. melanogaster (Biondi et al 2020).…”
Section: Discussionmentioning
confidence: 66%
“…Recent studies increase the general concern about insecticide resistance in D. suzukii advocating the application of sustainable pest control methods (Gress and Zalom 2019). Biological control is a promising route to reduce D. suzukii infestation using natural enemies and insect pathogens (Becher et al 2018;Biondi et al 2020;Daane et al 2016;Gabarra et al 2015;Lee et al 2019;Wolf et al 2020). Findings on the specificity of parasitoids with respect to Drosophila host species, different fruit species as well as fruit ripeness give grounds for hope toward the development of biological control (Girod et al 2018;Wolf et al 2020;Biondi et al 2020;Seehausen et al 2020).…”
Section: Discussionmentioning
confidence: 99%